Internal factors related to perceived performance-based corporate culture of large and medium-sized enterprises from employee perspective in Haidian district, Beijing - Wei, Yidong (2007)
The objective of this study is to identify the factors related to performance-based corporate culture and find the relationship between these factors and performance-based corporate culture in large and medium-sized companies in Beijing. Four of these factors are leadership, employee motivation, innovation and market orientation through previous scholars' research and they should positively be related to performance-based corporate culture according to hypotheses. This study also wants to test whether moderate variables ( age, gender and education) can slightly impact the relationship between independent variables and dependent variable. For this purpose, 188 questionnaires were collected and analyzed by statistical tool. Toe results shows that leadership, employee motivation, innovation and market orientation can significantly be related to performance-based corporate culture and this relationship is not able to be influenced moderately by age, gender and education referred to respondents. As a result, this research suggests that companies or organizations should concentrate on leadership, employee motivation, innovation and market orientation these four aspects of internal management in order to build strong performance-based corporate culture.